Analysis of Curriculum Planning by Using Importance Performance Analysis Technique - Amanah, Nur; Mujahidin, Endin; Andriana, Nesia (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2022)
Curriculum is an essential part of education. It has two functions in education, that are to realize the vision of education as well as become the reference of the implementation of education. Because of the importance of curriculum, school as an institution that manages the process of education must carry out curriculum planning that can be perceived by the teachers so that it can be implemented in the teaching and learning process. The objective of this research was to analyze the curriculum planning based on the importance and performance by Importance Performance Analysis. The data collection was done by random questionnaire given to 30 teachers in an elementary school, SD Islam dan Leadership Bintang Cendekia. From this research, it was found 8 very satisfying important attributes, 4 poor important attributes, and 6 poor unimportant attributes, and 2 very satisfying unimportant attributes.